Hypoxia promotes EV secretion by impairing lysosomal homeostasis in HNSCC through negative regulation of ATP6V1A by HIF‐1α. Issue 2 (7th February 2023) - Wang, Xiaoning; Wu, Ruoyi; Zhai, Peisong; Liu, Zheqi; Xia, Ronghui; Zhang, Zhen; Qin, Xing; Li, Chuwen; Chen, Wantao; Li, Jiang; Zhang, Jianjun
Abstract: Tumour cells under hypoxia tend to modulate the number and contents of extracellular vesicles (EVs) to regulate the tumour microenvironment (TME) and thus promote tumour progression. However, the mechanism of how hypoxia influences the secretion of EVs remains to be elucidated. Here, we confirm the increased production of EVs in head and neck squamous cell carcinoma (HNSCC) cells under hypoxia, where endosome‐derived EVs are the main subtype affected by insufficient O2 . The accumulation of hypoxia‐inducible factor‐1α (HIF‐1α) under hypoxia directly downregulates the expression of ATP6V1A, which is pivotal to maintain the homeostasis of lysosomes. Subsequently, impaired lysosomal degradation contributes to the reduced fusion of multivesicular bodies (MVBs) with lysosomes and enables the secretion of intraluminal vesicles (ILVs) as EVs. These findings establish a HIF‐1α‐regulated lysosomal dysfunction‐EV release axis and provide an exquisite framework to better understand EV biogenesis.